Have Students Comprehended Investment? - Paskanova Christi Gainau (Journal of Accounting and Investment, 2020)
Research aims: This study aims to examine factors that influence stock investment intention among students.Design/Methodology/Approach: The population in this study are all individual student investors registered at the Indonesia Stock Exchange Investment Gallery in the North Sulawesi and Gorontalo Regions. Sample selection is based on the purposive sampling method. Data analysis was performed with SmartPLS 3.0 M3.Research findings:  The results found that student attitudes are determined by employment opportunities in the capital market. In addition, attitudes and behavioral control also have significant effect on student intention. This is different with subjective norms which does not affect student investment intention.Theoretical contribution/ Originality: This research confirm that job opportunity influences students attitude in stock investment. The attitude and perceived behavioral control support students intention to invest stock in capital market.  Subjective norms does not effect to students intention, in the context of students in the North Sulawesi and Gorontalo Regions.Practitioner/Policy implication: The implication is the universities need to make policies which is friendly with stock investment, such us Seminars, Workshops, Capital Market Schools, and Securities Traders Representative Courses (WPPE). The Indonesian Stock Exchange (Representative Office) and Exchange Members also need to increase an internship quota in order to support student investment intentions.Research limitation/Implication: This study only examines the stage of student intentions because the sample is student whose main activity is studying and the additional activity is investing.